2020
DOI: 10.1093/rheumatology/keaa408
|View full text |Cite|
|
Sign up to set email alerts
|

Intestinal and enthesis innate immunity in early axial spondyloarthropathy

Abstract: Axial SpA (axSpA), encompassing AS, is a multifactorial disease that localizes to sites of high spinal biomechanical stress. Much has been written on T cells and adaptive immunity in axSpA, which is understandable given the very strong HLA-B27 disease association. Extra-axial disease characteristically involves the anterior uveal tract, aortic root, lung apex and terminal ileum. Under recent classification, axSpA is classified as an intermediate between autoimmunity and autoinflammatory disease, with the latte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 83 publications
0
12
0
1
Order By: Relevance
“…Indeed, a reevaluation of MRE in a cohort of children with IBD showed that, using the ASAS (Assessment of SpondyloArthritis international Society) criteria for signs of sacroiliitis, 15% of patients have mild sacroiliitis at MRE despite not complaining of any musculoskeletal symptoms [ 45 ]. The link between IBD and joint/bone inflammation might rely on the alteration of IL-23 and/or IL-17 axis, dysbiosis, and subclinical gut barrier dysfunction as well as genetic factors such as the HLA B27 positivity and NOD2 variants [ 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a reevaluation of MRE in a cohort of children with IBD showed that, using the ASAS (Assessment of SpondyloArthritis international Society) criteria for signs of sacroiliitis, 15% of patients have mild sacroiliitis at MRE despite not complaining of any musculoskeletal symptoms [ 45 ]. The link between IBD and joint/bone inflammation might rely on the alteration of IL-23 and/or IL-17 axis, dysbiosis, and subclinical gut barrier dysfunction as well as genetic factors such as the HLA B27 positivity and NOD2 variants [ 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the purposes of this article the term SpA was taken to include the protean manifestations associated with axial inflammation including skin and gut involvement where it has clearly been shown that IL-23 SNPs are a common denominator across the different conditions. It is also clearly evident in experimental and human systems that the IL-23/IL-17 axis is involved in skin, gut and entheseal biology ( 90 ). A differential immunopathology exists within these disease domains reflecting the context dependent biology of different tissues that is currently best understood in terms of the barrier function role of IL-17A in the gut.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the damage-associated molecular patterns (DAMPs) from highly biomechanically stressed entheses can disturb “fine tuning” of cytokine production in homeostatic entheseal tissues. The net-effect of these processes may serve as key drives for the onset, evolution, sustenance, flare-up, and eventual outcomes of r-AxSpA ( Sharif et al, 2020 ). The cellular and molecular bases for enthesitis in AS patients are illustrated in Figure 5 .…”
Section: Pathogenesis Of Enthesitis In As Patientsmentioning
confidence: 99%